2021
DOI: 10.1021/acsomega.1c03728
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Anisotropic Carrier Mobility for Two-Dimensional Nb2Se9 Material

Abstract: Finding new materials with satisfying all the desired criteria for nanodevices is an extremely difficult work. Here, we introduce a novel Nb 2 Se 9 material as a promising candidate, capable of overcoming some physical limitations, such as a suitable band gap, high carrier mobility, and chemical stability. Unlike graphene, it has a noticeable band gap and no dangling bonds at surfaces that deteriorate transport properties, owing to its molecular chain structure. Using density functional theory (DFT) calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…We find that the monolayers considered in this work exhibit anisotropic carrier mobility, similar to that reported in other 2D materials such as phosphorene, PC 6 , group IVB dichalcogenide monolayers, etc. 26,[33][34][35][36][37][38][39][40][41] (see Table S4 in the ESI †). MoGe 2 P 4 is the most anisotropic monolayer, with the ratio of mobilities along the zigzag and armchair directions being ∼3.6.…”
Section: Introductionmentioning
confidence: 99%
“…We find that the monolayers considered in this work exhibit anisotropic carrier mobility, similar to that reported in other 2D materials such as phosphorene, PC 6 , group IVB dichalcogenide monolayers, etc. 26,[33][34][35][36][37][38][39][40][41] (see Table S4 in the ESI †). MoGe 2 P 4 is the most anisotropic monolayer, with the ratio of mobilities along the zigzag and armchair directions being ∼3.6.…”
Section: Introductionmentioning
confidence: 99%
“…It can be found that the hole mobilities of the 1D NbS 4 nanowire is 316.63 cm 2 V À1 s À1 , which is larger than other 1D materials, such as Nb 2 Se 9 (2.5), 22 Ta 2 Ni 3 Se 8 (42.9), 23 X V Y VI Z VII (X = As, Sb, and Bi; Y = S, Se, and Te; Z = Cl, Br, and I) (ranging from 5.25 to 27.29), 27 InSeI (54.17), 96 Sn 2 S 3 (33.9) and Sn 2 Se 3 (309.1), 83 SbSeI (6.84) and SbSI (23.41) as well as SbSBr (0.64). 95 And the electron mobility of 1D NbS 4 nanowire is 111.9 cm 2 V À1 s À1 , which is larger than that of most reported 1D materials, such as Nb 2 Se 9 (41.9), 22 Ta 2 Ni 3 Se 8 (59.6), 23 most of X V Y VI Z VII (X = As, Sb, and Bi; Y = S, Se, and Te; Z = Cl, Br, and I) (ranging from 16.43 to 322.95), 27 Sn 2 S 3 (63.5), Sn 2 Se 3 (85.9), 83 SbSeI (25.69), SbSI (54.55), SbSBr (96.68), 95 and InSeI (27.49). 96 Furthermore, the carrier mobility of the 1D NbS 4 nanowire exhibits obvious anisotropy, manifesting that the hole mobility is approximately three times larger than the electron mobility.…”
Section: The Stability Electronic Structure and Optical Properties Of...mentioning
confidence: 85%
“…For van der Waals materials, different band gap values and transport properties are common in the bulk phase and their isolated low-dimensional counterparts. The transformation of bandgap properties is also revealed with decreased dimension in the quasi-1D material Nb 2 Se 9 of the same family, 22,91 which is mainly attributed to the redistribution of electron density caused by the reduced dimensionality as well as the changed dispersion relationship. Moreover, the dimensionality reduction imposing quantum confinement on the electrons of the nanowires also plays a role in the indirect-todirect band gap transition from the bulk phase to a single nanowire.…”
Section: The Stability Electronic Structure and Optical Properties Of...mentioning
confidence: 91%
See 2 more Smart Citations